Dosimetry Audit of IMRT and VMAT External Radiotherapy Techniques: Multi-Institutional Study in East Java Province - Maqsuroh, Fiki Hurum; Zahro, Ummu Mar’atu; Dzulfikar, Ahmad Zaki; Harfiyyah, Vivin Fashihatil; Hentihu, Fatimah Kunti; Pawiro, Supriyanto Ardjo (Indonesian Journal of Cancer, 2025)
Background: The Multi-Leaf Collimator (MLC) application is utilized in the Linear Accelerator (LINAC) with Intensity Modulated Radiotherapy (IMRT) and Volumetric Modulated Arc Therapy (VMAT) methods, both of which include advanced methods of administering radiotherapy, which aim to improve dose distribution and increase local tumour control by adjusting the external beam into a shape-specific tumour. Dosimetry audit is a crucial quality assurance procedure in radiotherapy facilities, ensuring patient dosing quality. This study aimed to simulate the dosimetry audit method of IMRT techniques and VMAT with point dose and dose delivery distribution evaluation. Method: The phantom utilized in this study was constructed from acrylic material and featured a C-shaped insert. It comprised a main body and an insert, with the body measuring 15 × 15 × 15 cm and the insert measuring 6 × 6 × 6 cm. The main body was fabricated from polymethyl methacrylate (PMMA) with a density of 1.17 g/cm³, serving as a surrogate for human tissue. The insert, composed of a resin and carbon powder mixture with a density of 1.19 g/cm³, was designed to represent both the organ at risk (OAR) and the planning target volume (PTV) in the study. Phantom images were taken with the center of the CT simulator, then radiation planning was performed with a PTV dose of 4 Gy/2 fractions (D95% 95%, D2% 107%, and Dmax 110%) and a maximum OAR dose of 2.8 Gy. This study was conducted at four radiotherapy centres in East Java province by conducting dosimetry audits on point doses using TLD and dose distribution by evaluating gamma index analysis using EBT3 Film.Results: The results of point dose readings using TLD at all centres and radiation techniques were still within the tolerance limit, namely ± 5%. Apart from that, to evaluate the gamma index using film, at three centres with the 3%/3mm criteria, the gamma passing rate was 90%. Conclusion: This method can be used as a reference in conducting dosimetry audits in radiotherapy using TLD and film